Tinjauan Kriminologi Terhadap Pemerkosaan Akibat Perilaku Seks Bebas di Kalangan Remaja - A. Nurfachrul Ismail; Tri Suhendra Arbani (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
This study raises one problem of juvenile delinquency. Wearing teens, which is usually only done in big cities, now includes small areas, such as Sinjai District. In Sinjai itself, juvenile delinquency is increasing day by day, the sense of knowledge and the culture of wanting to be said makes teenagers seem to want to compete in doing, the most dangerous thing committed by teenagers is the act of rape due to promiscuity. The act of rape has been regulated in Article 285 of the Criminal Code and Article 81 paragraph 1 of Law no. 22 of 2002 concerning Child Protection. The purpose of this study was to look at the factors that influence free sex behavior in adolescent groups and to measure the measures taken to reduce rape due to casual sex among adolescents. The type of research used is descriptive qualitative in which the research generally describes the object discussed in accordance with the data obtained through interviews and others using the Sociological Normative approach. The data sources used in this research are primary and secondary, then the information method used is to collect good data through interviews, books, magazines, websites, and documents.